GAMBARAN KARAKTERISTIK PASIEN BENIGN PROSTATIC HYPERPLASIA DI RUMAH SAKIT UMUM DAERAH LUBUK PAKAM KABUPATEN DELI SERDANG - Batara Simangunsong; Juli Jamnasi (Universitas Methodist Indonesia, 2017)
Background. Benign prostatic hyperplasia (BPH) is a form of histological abnormality of the enlarged prostate gland where there is a proliferation of stromal cells in the prostate. Clinical manifestations of BPH disease can include disruption of urine flow (micturition), difficulty urinating and the desire to urinate but the urine is weak. BPH is a problem commonly suffered by men over the age of 60 years. This study aims to get a description of the characteristics of BPH patients in Lubuk Pakam General Hospital on the Deli Serdang Regency for period of 2016-2017. Methods. This research is a retrospective descriptive study with a cross-sectional design in Lubuk Pakam General Hospital on the Deli Serdang Regency, North Sumatra, from January 2016 to December 2017. Using the total sampling technique obtained 95 samples based on inclusion and exclusion criteria. Data obtained from medical records. Results. The most age-based BPH patients were the 61-70 year age group, 41 people (43.2%). The prostate volume in most BPH patients are in the prostate volume group > 60.00-80.00 ml which are 29 people (30.5%). BPH sufferers based on the most symptoms are complaints are difficult urination of 36 people (37.9%). Summary. Based on the results of research in the medical record Installation of Lubuk Pakam General Hospital on the Deli Serdang Regency for the period of January 2017-December 2018, it can be concluded that the most age group of BPH patients is the age group 61-70 years. And the main clinical symptoms s most often found are difficult urinating.